1068 Can Loss of Sleep-Awake Cyclicity at Aeeg Predict Posthemorrhagic Hydrocephalus in Preterm Infants with Intraventricular Hemorrhage?. (October 2012) - Scoppa, A; Pozzi, N; Pallante, C; Boffa, F; Orfeo, L
Abstract : Background and Aim: Intraventricular hemorrhage (IVH) is the most common brain injury in preterm infants. Among infants with IVH 30% develops posthemorrhagic hydrocephalus (PPH). Actually there is no predicting factor for the developing of PPH. We observed if loss of sleep-awake cyclicity, at aEEG evaluation, is predictive for PPH. Methods: 6 preterms of gestational age between 25 and 30 weeks were detected for IVH (II degree to IPH) at cerebral ultrasonography. Cerebral background activity was continuously performed by CFM (Brainz US). Results: Sleep-awake ciclicity was observed in all 6 infants in the first 24 hours after the detection of IVH. But in 2 of these we noted the loss of cyclicity few days after the diagnosis of the bleeding. These 2 patients developed posthemorrhagic hydrocephalus whereas the other 4 infants didn′t develop PPH. Conclusions: Loss of sleep-awake cyclicity, at aEEG, has a high positive predictive value for the developing of PPH in preterm infants with IVH; therefore study of cerebral background activity and in particular of sleep-awake cyclicity can be used as a early prognostic tools in patients at risk of PPH.